Compliance in Teams - Implications of Joint Decisions and Shared Consequences - Tim Lohse; Sven A. Simon (Center for Economic Studies and ifo Institute (CESifo), 2019)
In today's business environment, team work is omnipresent. But might teams be more prone toward non-compliance with laws and regulations than single individuals despite imminent neg-ative consequences of uncovering misconduct? The recent prevalence of corporate delinquencies gives rise to this concern. In our laboratory experiment, we investigate the determinants of teams' compliance behavior. In particular, we disentangle the effect of deciding jointly as a team of two from sharing the economic consequences among both team members. Our findings provide evidence that teams are substantially less compliant than individuals are. This drop in compliance is driven by the joint, rather than the individual, liability of team members. In contrast, whether subjects make their decisions alone or together does not influence the overall compliance rate. When coordinating their compliance decision teams predominately discuss the risk of getting caught in an audit, and team decision-making is characterized by behavioral spillovers between team members. Holding each team member fully liable is a promising means to deter them from going astray.
Keywords: C92; D91; K42; 330; compliance; lying; team decision; shared liability; audit; communication; laboratory experiment